Определение приоритетов местного самоуправления в инфраструктуре здравоохранения с использованием метода аналитической иерархии: Пример местных органов власти в провинции Западная Ява - Б. Харизма; С. Реми; А. Нур (Вопросы государственного и муниципального управления, 2019)
Infrastructure and health are considered to be crucial investments in many countries in order to sustain their economic growth, including Indonesia. Furthermore, after decentralization in 2001, Indonesian local governments have had the authority to expand both sectors in order to support the acceleration of national economic growth. However, policymakers in the regions are often confronted with many factors in the investment decision-making process, one of which is budget constraints. Therefore, this study aims to prioritize policy in the healthcare infrastructure sector determined by local government administrators in West Java province. A benefit-cost approach was used as an element for characterizing the positive and negative impacts (benefit for positive impact, and cost for negative impact) by period and categories to set the projects’ prioritization which was measured by Analytical Hierarchy Process (AHP). The result shows that the majority of policy makers in the regions provide an assessment with the highest cost-benefit ratio for public health enhancement compared with other alternatives. This means that accessibility to primary healthcare facilities is still the main focus for prioritization and local government administrators prefer to focus on policy where the impact is to increase the health enhancement through expanding coverage of primary health facilities in the sub-district areas. As a policy recommendation, AHP was demonstrated for the effectiveness in the decision-making process for public budgeting, especially in terms of infrastructure investment.